2011
DOI: 10.1016/j.apsusc.2010.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Co removal and phase transformations during high power diode laser irradiation of cemented carbide

Abstract: Abstract.The use of a continuous wave-high power diode laser for removing surface Co-binder from Cocemented tungsten carbide (WC-Co (5.8 % wt.)) hardmetal slabs was investigated. Combined scanning electron microscopy, energy dispersive X-ray spectroscopy and X-ray diffraction analyses were performed in order to study the phase transformations and micro-structural modifications of the WC-Co substrates occurring during and after laser irradiation. The micro-structure of the WCCo progressively transforms as energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…Etching with chemical solutions is often needed to remove oxides and/or contaminants which are generated during laser treatments [29]. 940 nm continuous high power diode laser can be also used to pretreat the Co-cemented tungsten carbides prior to diamond deposition [11,12]. In order to prevent Co and W oxidation, the substrates can be placed in a protective chamber and flushed with pure Ar or N 2 (99.999%).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Etching with chemical solutions is often needed to remove oxides and/or contaminants which are generated during laser treatments [29]. 940 nm continuous high power diode laser can be also used to pretreat the Co-cemented tungsten carbides prior to diamond deposition [11,12]. In order to prevent Co and W oxidation, the substrates can be placed in a protective chamber and flushed with pure Ar or N 2 (99.999%).…”
Section: Methodsmentioning
confidence: 99%
“…A glass window at the top of the chamber allows delivery of laser irradiation and inspection. Laser power can be in the range of 500-1500 W, and scan speed is typically set at 1 mm/s [11]. The beam is moved back and forth along linear and parallel patterns to uniformly cover the entire substrate surface with an overlap of ∼0.5-1.0 mm between two consecutive linear patterns.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, some of the authors have used a continuous wave-high power diode laser source to modify the surface chemical composition and morphology of as-ground hard metals . To prevent Co and WC oxidation, they performed the laser treatments in pure Ar atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the proper adjustment of the laser processing parameters allowed the selective removal of Co from the outermost layer of WC–Co, the recrystallization and coarsening of WC surface grains with consequent surface roughening, and the relief of microstrains induced in WC–Co by the grinding process. Following this, the present investigation is aimed to (i) validate the laser treatment of hard metal substrates described in ref ; (ii) study the hot filament chemical vapor deposition (HFCVD) of diamond coatings onto WC–Co substrates pretreated by continuous wave-high power diode laser; (iii) evaluate the effect of different inert gases (namely, Ar and N 2 ) on both the substrate surface morphology that develops upon laser irradiation and coating adhesion; (iv) compare the wear resistance of diamond coatings grown onto laser treated substrates and onto substrates subjected to a well-known two-step wet chemical etching pretreatment, employing Murakami’s reagent and Caro’s acid…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation